Rise of tuberculosis globally after a decline - Zafar, Nazia; Khaliq, Rameen; Memon, Midori (Journal of the Pakistan Medical Association, 2023)
Dear Madam, Tuberculosis is an infectious disease caused by Mycobacterium Tuberculosis that primarily affects the lungs and spreads via respiratory droplets from person-to-person contact. Tuberculosis has remained endemic in Pakistan for many decades despite the preventative measures taken. With an overwhelming population of 179.6 million, Pakistan ranks fifth amongst the countries with the highest TB burden. 63% of TB cases come from Pakistan in the eastern Mediterranean region. Furthermore, according to the National Tuberculosis Control Program (NTP), 413,450 TB cases (of all types) occur in Pakistan each year, with an incidence of 231 per 100,000 people. According to the NTP, the prevalence of tuberculosis is 630,000 cases (364/100,000 people), with mortality rates in the 60,000 (34/100,000 people) range. [1] The enormity of the population, coupled with a lack of trained medical personnel and the shortage of medical facilities provided, especially in rural areas, makes it extremely difficult to detect and treat the patients. Pakistan already has a fragile healthcare system, and with the addition of the covid 19 pandemic, tuberculosis seems to be on the rise more than ever. Because of the acute and rising burden of the pandemic, the priorities were shifted. Interruptions in regular outpatient services caused by government-mandated lockdowns, general fear of visiting hospitals, and redirection of TB-specific facilities all attributed to the deterioration of case management of TB detection, allowing countless cases to go undiagnosed. [2] The World health organization’s 2022 Global TB report showed that 10.6 million people were diagnosed with tuberculosis in 2021, a staggering increase of %t from the previous year. Approximately 1.6 million people lost their lives to this disease. From 2021 to 2022, the burden of drug-resistant TB increased of 3%, coupled with 450 000 additional cases of rifampicin-resistant tuberculosis (RR-TB) in 2021. [3] As the burden of the pandemic and other infectious diseases, such as poliomyelitis, are still under scrutiny, we need to put more efficient measures to come up with new systems to prevent and lessen the burden of TB, especially when there is a marked global rise in cases.